2012
DOI: 10.1088/0965-0393/20/4/045008
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale simulation of microstructure evolution during multi-stage hot forging processes

Abstract: The paper presents a two-dimensional cellular automaton (CA) approach coupled with a topology deformation technique for quantitative and topographic prediction of the microstructure evolution during multi-stage hot forging processes. The simulation presented in this work was implemented by an in-house developed C++ program. The grain topography, recrystallization fraction and average grain size were also obtained during a four-hit forging process. The simulated results agree well with the experimental data in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Generally speaking, the CA framework for recrystallization has the similar form which is composed of the following parts [79,93]:…”
Section: Implementation Of Recrystallization In the Ca Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, the CA framework for recrystallization has the similar form which is composed of the following parts [79,93]:…”
Section: Implementation Of Recrystallization In the Ca Modelmentioning
confidence: 99%
“…These features indicate that it is possible to model the microstructure evolution within a unified frame [64][65][66]. In contrast to the limited applicability of the macro-scale models, e.g., the phenomenological model and the statistical model, this characteristic of mesoscopic models also shows the latent advantage of the numerical solution of the complexity of microstructural evolution globally , such as normal grain growth [68][69][70][71][72][73][74][75][76], recrystallization [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98] and phase transformation [100][101][102][103]. 4.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for such a difference may be because that the elongated grain boundaries provide more potential nucleation sites for recrystallization due to a higher ratio of the grain boundary volume to grain volume. At the same time, the newly formed recrystallized grains impinge earlier with support of the morphology change of the matrix, resulting in a smaller average grain size as compared to the conventional CA simulation [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In addition, it can be also found that the grain morphology deformation has a decreased effect on the critical strain for DRX.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…(4) can be determined for a deforming material. Second, the constant C dynamic can be determined using an inverse analysis method [9,14]. The dislocation density of recrystallized grain evolves from zero to a saturated value.…”
Section: Modeling Of Nucleation and Grain Growthmentioning
confidence: 99%
See 1 more Smart Citation